IMPLEMENTASI MODEL PEMBELAJARAN AKTIF DALAM PAI DI ERA KURIKULUM MERDEKA - Zainuri, Habib; Aria Yudiarta, Lutfhy; Latif, Baharudin (IAIN Madura, 2025)
The curriculum is a fundamental component of education that formulates the objectives, content, and learning activities. The method used in this article is a literature review, which involves collecting data by understanding and analyzing theories from various relevant sources. The utilization of instructional media that supports learning requires teachers to have the skills to select and use media that facilitate active learning methods. The implementation of active learning models in Islamic Religious Education (PAI) within the context of the Merdeka Curriculum era has a positive impact on enhancing student engagement, 21st-century skills, and a more relevant understanding of religion in real life.